Practicing the Sensitivity of Social Life to Chemical Engineering Students Through Cooperative Learning - Fatmawati, Akbarningrum; Suseno, Natalia; Hwa, Lie; Edrika, Ivonne (Faculty of Psychology, Universitas Surabaya, 2008)
Students from several regions of Indonesia who come to study in Surabaya encounter new challenges in their academic life, which are not easy to deal with. In order to be ready to face these challenges, they need to be equipped with values for social life (such as teamwork) so that they are able to survive in their academic and social life. Acombined cooperative learning and jigsaw method conducted in Thermodynamics 1 Class was meant to cultivate positive values of teamwork such as positive interdependence and individual accountability. Participants (N = 58) were Thermodynamics 1 class, which was divided into 15 groups to work on class assignments and laboratory projects. The en- thusiasms of the students in class were shown by 89% minimum attendance of each activity.About 61% of the students reached their individual mid-term targets, showing a 10% increase if compared to the preceding semester result. Mahasiswa dari berbagai daerah di Indonesia yang belajar di Surabaya menghadapi tantan- gan baru yang tak mudah diatasi dalam kehidupan akademiknya. Agar siap menghadapi beraneka tan- tangan tersebut, mereka perlu dilengkapi dengan nilai-nilai kehidupan sosial (seperti kerja sama) se- hingga mereka mampu bertahan dalam kehidupan akademik dan sosialnya. Sebuah kombinasi metode pembelajaran kooperatif dan jigsaw diterapkan pada kelas Termodinamika 1 untuk menumbuhkan ni- lai-nilai positif kerja sama seperti kesaling- tergantungan yang positif dan akuntabilitas pribadi. Peser- ta (N = 58) adalah kelas Termodinamika 1, yang dibagi menjadi 15 kelompok untuk menyelesaikan tugas-tugas kelas dan proyek laboratorium. Antusiasme para mahasiswa dalam kelas tercermin dari miniumum kehadiran yang 89% pada tiap aktivitas. Sekitar 61% mahasiswa mencapai target UTSnya, menujukkan kenaikan 10% bila dibandingkan dengan hasil semester sebelumnya.